1997
DOI: 10.5144/0256-4947.1997.10
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Breast Cancer

Abstract: retrospective review of all female breast cancer cases treated at KFSH&RC over a 15-year period. Patients were divided into two groups at the time of their referral to KFSH&RC: metastatic and nonmetastatic. We describe the demographic data, cancer-related information and the treatments offered to all patients. Comparisons were made between Saudi and non-Saudi, and the Saudis were examined in relation to their region of referral and observed to see if any changes occurred during the study period. As well, we tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Sixty-two percent of women with breast cancer listed in the 1996 JCR were less than 53 years old. Although different from the age distribution of breast cancer cases in most of the Western countries (Stone, 1997), the findings are similar to the distribution of cases reported in a recent national study done in Saudi Arabia (Ezzat et al, 1997) and in the West Bank and Israel (Barak et al, 1988). nine times higher for users than for nonusers (OR=8.62, CI=3.33-22.28), with an increased risk among older women.…”
Section: Discussionsupporting
confidence: 70%
“…Sixty-two percent of women with breast cancer listed in the 1996 JCR were less than 53 years old. Although different from the age distribution of breast cancer cases in most of the Western countries (Stone, 1997), the findings are similar to the distribution of cases reported in a recent national study done in Saudi Arabia (Ezzat et al, 1997) and in the West Bank and Israel (Barak et al, 1988). nine times higher for users than for nonusers (OR=8.62, CI=3.33-22.28), with an increased risk among older women.…”
Section: Discussionsupporting
confidence: 70%
“…Ezzat et al , in an analysis of 801 Saudi women for the period 1986–1991, found 26% (206/801) had stage four cancer [43]. Of the 595 patients with cancer stages one to three (Table 2), 67% were lymph node positive with 34% having greater than four lymph nodes involved [43]. Ibrahim et al identified a median age at presentation of 42 years with 78% younger than 50 years [44].…”
Section: Resultsmentioning
confidence: 99%
“…Ezzat et al reported that 33% of cases were ER+ and 28% (n = 271) were PR+ [43]. In a further study of 145 patients, positive Her-2 expression (3+) was observed in 28% of patients and correlated inversely with ER status [54].…”
Section: Resultsmentioning
confidence: 99%
“…In 1994, 437 cases were reported in the country. 1 At King Faisal Specialist Hospital and Research Centre (KFSH&RC), 1723 patients with breast cancer were treated between 1975 and 1991. 1 We currently receive 250-300 new cases every year.…”
mentioning
confidence: 99%
“…1 At King Faisal Specialist Hospital and Research Centre (KFSH&RC), 1723 patients with breast cancer were treated between 1975 and 1991. 1 We currently receive 250-300 new cases every year. Every new patient is assessed by a team composed of a medical oncologist, a radiation oncologist and a surgeon.…”
mentioning
confidence: 99%